A survey regarding zero burning policy among smallholders for oil palm plantation in Jasin / Mohammad Dzulkeflee Roslan - Roslan, Mohammad Dzulkeflee (Faculty of Plantation and Agrotechnology, 2018)
Zero-burning policy is a policy that been made by RSPO and it is included in principle number 5 which is the environmental responsibility and conservation of natural resources and biodiversity. Zero-burning is a practice of land clearing without involving the use of fire to remove the oil palm tree residue. This zero-burning practice is important to be carry out to avoid from causing damage to the environment and to create a sustainable production of oil palm. This survey is carried out to identify the awareness of smallholders in zero-burning policy. This survey is also carried out to determine the factors that affecting the awareness towards zero-burning policy among smallholders. From this survey also can identify the implementation of zero-burning among smallholders in Jasin and the factors that may become the cause for the smallholders unable to carry out zero-burning practice. The dependent variable in this project is the awareness of smallholders regarding zero-burning policy while the independent variables are knowledge, attitude and affordability of smallholders. This survey is carried out at Jasin, Melaka. The total respondents for this survey is 73 respondents. The data obtained from the survey were analyzed using Statistical Package for Social Science (SPSS) to carry out the descriptive, multiple regression and correlation coefficient. Results shows that majority of the smallholders in Jasin are aware of zero-burning policy but they did not implement this policy in their oil palm field. The factors for not being able to carry out the practice is because of large capital required and the presence of dangerous animal in their oil palm field due to oil palm tree residue. From the result also have determine that the most influence factors towards the awareness is knowledge of smallholders regarding zero-burning policy. The recommendation for this project is, the government and other related agencies have to plays their vitals roles in implementing this zero-burning policy especially among the smallholders. They could come out with a new idea on how to encourage the smallholders to implement zero-burning practice in their field. This is important to be done to produce a sustainable oil palm production.